Agreement between the United Kingdom of Great Britain and Northern Ireland and the Republic of Poland on the Participation in Certain Elections of Nationals of Each Country Resident in the Territory of the Other, Warsaw, 29 May 2020. ([2020-06-08]) - Unknown
No abstract available